Outpatient Nutritional Care Project: Experience Report in Pandemic Times (Citizenship in Action: Extension and Culture Magazine, 2024)
This is an Experience Report of an Extension Project that aimed to encourage the active participation of individuals in the joint search for better life habits according to their individual health needs, through scientific content on social medias. From October to December 2020 and June to December 2021, the Outpatient Nutritional Care Project was developed and implemented, through educational actions on nutrition remotely, caused by the global pandemic of COVID-19. As the project needed to reinvent itself, it was then decided to make the activities online and disseminate content through the social medias Instagram and Facebook to academic and non-academic circles. 914 people were reached on social medias, being 734 people on Instagram and 180 on Facebook. There were a total of 9.719 public interactions with the content published in the aforementioned period, which included topics on Obesity, Vegetarianism, Diabetes mellitus, Food and Nutrition Security Policy, Nutrition and Athletes, among others. In this way, the actions carried out showed the possibility of new pedagogical forms of reprotuction, production and socialization of knowledge through remotete aching, making the practice and experience of interdisciplinarity effective.
Keywords: nutritional Sciences; Covid-19; quality of life; social networking